Pendampingan Kajian Agama dan Wawasan Keagamaan dalam Meningkatkan Spiritual Siswa SMK - Miftaku Ni'amah; Asfahani Asfahani; Muhajir Musa; Liza Husnita (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
Religious studies and religious insight at Gula Rajawali Vocational School are directed at providing constructive solutions in shaping student character, through targeted and relevant assistance. This service aims to create an educational environment that supports students' spiritual development, fosters religious values, and makes a positive contribution to the character formation and welfare of students at Gula Rajawali Vocational School. The method used in carrying out this service is participatory story action research (PAR). The results of this service research show that the mentoring program for religious studies and religious insight at Gula Rajawali Vocational School succeeded in providing a significant positive impact on increasing students' spiritual dimensions. So, this program not only creates a deeper awareness of religious values, but also integrates spiritual aspects into the vocational learning environment, contributing to the holistic development of students.